CREDIT SOLVENCY OF AGRICULTURAL COMPANY AS A FACTOR OF QUALITY MARKET POSITION - Vasiljevic, Aleksandar; Novkovic, Nebojsa (Economics of Agriculture, 2006)
The main target of agriculture is to make the profit and the food production represents the function of agriculture. The economic and financial strength of agriculture system –producers is main paramether market position and verification in conditions of market economy and more and more agresive foreign competitors. In actual conditions of domestic agriculture, the credit relations is necessary in process of reguilar mainteance and activity of system. The credit relations are represent in relations with suppliers, lizing companies, banks and other participants in legal transfer. In process of establishing the credit relations with agricultural systems the most important factors which influences on quality and conditions of credit relations are: the biological caracter of production and strong influence of naturale factors on results of production, the season caracter of production, slow turnover of capital and different economic justification between some of production lines. Getting the quality credit position is not the act, already it is the process in which the system is making the own picture. If the system is better positioned on the market from the aspect of credit solvency, it can expect better credit relations (the risk of investment in credit capable systems is less). In process of getting the better credit solvency the need is to valuate some of ballast, and the most important are: preserving the current liquidity, preserving the real value of capital and resource and getting the financial counterweight.